6-3x=-2x

Thank you for the opportunity to help you with your question!

6 - 3x = -2x

step 1. Add 3x to both sides

6 - 3x + 3x = -2x + 3x

step 2. simplify both sides

6 = 1x

So x=6

double check by substituting 6 for x

6 - 3 (6) = -2 (6)

6 - 18 = -12

-12 = -12 CHECKS OUT, so x=6 is correct

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up